Influence of surface preparation on atomic layer deposition of Pt films - 葛亮 胡成 朱志炜 张卫 吴东平 张世理 (Journal of semiconductors, 2012)
We report Pt deposition on a Si substrate by means of atomic layer deposition（ALD） using（methylcyclopentadienyl） trimethylplatinum（CH_3C_5H_4Pt（CH_3）_3） and O_2.Silicon substrates with both HF-last and oxidelast surface treatments are employed to investigate the influence of surface preparation on Pt-ALD.A significantly longer incubation time and less homogeneity are observed for Pt growth on the HF-last substrate compared to the oxide-last substrate.An interfacial oxide layer at the Pt-Si interface is found inevitable even with HF treatment of the Si substrate immediately prior to ALD processing.A plausible explanation to the observed difference of Pt-ALD is discussed.